Significant effect of gender on hamstring-to-quadriceps strength ratio and static balance in prepubescent children from 7 to 12 years of age - Holm, I.; Vollestad, N. (The American Journal of Sports Medicine, 2008)
A number of studies have reported lower muscular strength of the hamstring and the quadriceps and better postural control in female compared with male athletes. Whether those differences are innate and also exist in children and adolescents or are caused by training and participation in different sports is unknown.